2020
DOI: 10.1002/ijfe.2173
|View full text |Cite|
|
Sign up to set email alerts
|

Outward foreign direct investment and economic growth in Romania: Evidence from non‐linear ARDL approach

Abstract: Globally, the outward foreign direct investment (OFDI) has significantly increased during recent years. In the light of OFDI's role in determining the GDP growth rate, it is necessary to assess how economic growth rate responds to such outflows. Based on the non-linear autoregressive distributive lag (NARDL) model, the present study investigates the long-run and short-run asymmetric impacts of OFDI on the economic growth in Romania covering the period 1990-2019. The results indicate that both an increase and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
3
17
1
Order By: Relevance
“…A modern approach to the nonlinear autoregressive distributed lag (NARDL) technique introduced by Shin et al (2014) was used in the study to explore short-and longterm asymmetries in the proposed variables. NARDL methods outperform conventional ARDL procedures in exploring cointegration using small data samples (Amin et al, 2022;Karim et al, 2022). Various studies have used this approach to explore outcome-dependent factors due to the contraction or enhancement of each explanatory factor (Bahmani-Oskooee and Ghodsi, 2017; Syed et al, 2021Syed et al, , 2022Ullah et al, 2021;Tang et al, 2022) The main model of Equation ( 3) is decomposed into asymmetric Equation ( 7) by substituting the pessimistic and optimistic sums of Equations ( 5) and ( 6).…”
Section: Methodology For Estimationmentioning
confidence: 99%
“…A modern approach to the nonlinear autoregressive distributed lag (NARDL) technique introduced by Shin et al (2014) was used in the study to explore short-and longterm asymmetries in the proposed variables. NARDL methods outperform conventional ARDL procedures in exploring cointegration using small data samples (Amin et al, 2022;Karim et al, 2022). Various studies have used this approach to explore outcome-dependent factors due to the contraction or enhancement of each explanatory factor (Bahmani-Oskooee and Ghodsi, 2017; Syed et al, 2021Syed et al, , 2022Ullah et al, 2021;Tang et al, 2022) The main model of Equation ( 3) is decomposed into asymmetric Equation ( 7) by substituting the pessimistic and optimistic sums of Equations ( 5) and ( 6).…”
Section: Methodology For Estimationmentioning
confidence: 99%
“… Ameer et al (2017) explored the nexus between FDIO and domestic capital formation particularly in the case of China and concluded that there exists a unidirectional positive long-run causality running from FDIO to aggregate domestic capital, however, a causality relationship does not exist in the short run. While, the results of Amin et al (2020) demonstrate that FDIO increases domestic output as well as overseas production to stimulate their competitiveness worldwide. Neoclassical theories consider that FDI is the crucial factor in the stimulation of domestic capital reserves in addition to the expansion in the total factor productivity 2 ( De Mello, 1997 ; Xu and Wang, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign direct investment (FDI) fulfills rising investment requirements to boost economic growth in developing countries ( Razzaq et al, 2021 ; Wu et al, 2021 ; Tang et al, 2022 ). Even though developed countries are the principal source of foreign direct investment outflows (FDIOs), developing economies have emerged as the leading sources of FDIO in the last three decades ( Knoerich, 2017 ; Amin et al, 2020 ; Xiang et al, 2022 ). Several multinational companies from developing and emerging countries are investing across the borders globally through FDI.…”
Section: Introductionmentioning
confidence: 99%
“…Some of determinants that has been found as significant for FDI outflow are policies in home country related to foreign trade, financial sector and investment development. [14] outflow also for enhancing their competitiveness. [15] All of these mentioned areas are the building stones of business environment, that surrounds the companies.…”
Section: Literature Reviewmentioning
confidence: 99%